Dual TNFα-induced effects on NRF2 mediated antioxidant defence in astrocyte-rich cultures: role of protein kinase activation - Correa, Fernando Gabriel (2012)
Tumor necrosis factor-α (TNFα) is a pleiotropic molecule that can have both protective and detrimental effects in neurodegeneration. Here we have investigated the temporal effects of TNFα on the inducible Nrf2 system in astrocyte-rich cultures by determination of glutathione (GSH) levels, γglutamylcysteine ligase (γGCL) activity, the protein levels of Nrf2, Keap1, the catalytic and modulatory subunit of γGCL (γGCL-C and γGCL-M respectively). Astrocyte-rich cultures were exposed for 24 or 72 h to different concentrations of TNFα. Acute exposure (24 h) of astrocyte-rich cultures to 10 ng/mL of TNFα increased GSH, γGCL activity, the protein levels of γGCL-M, γGCL-C and Nrf2 in parallel with decreased levels of Keap1. Antioxidant responsive element (ARE)-mediated transcription was blocked by inhibitors of ERK1/2, JNK and Akt whereas inactivation of p38 and GSK3β further enhanced transcription. In contrast treatment with TNFα for 72 h decreased components of the Nrf2 system in parallel with an increase of Keap1. Stimulation of the Nrf2 system by tBHQ was intact after 24 h but blocked after 72 h treatment with TNFα. This down-regulation after 72 h correlated with activation of p38 MAPK and GSK3β, since inhibition of these signalling pathways reversed this effect. The upregulation of the Nrf2 system by TNFα (24 h treatment) protected the cells from oxidative stress through elevated γGCL activity whereas the down-regulation (72 h treatment) caused pronounced oxidative toxicity. One of the important implications of the results is that in a situation where Nrf2 is decreased, such as in Alzheimer’s disease, the effect of TNFα is detrimental.